Bioprospecting of non-timber forest products of selected flora in Baluran National Park, East Java, Indonesia for phytochemicals, anti-diabetic, anti-tyrosinase, and antioxidants - RICO RAMADHAN; NI’MATUZAHROH NI’MATUZAHROH; DINDA AYU LESTARI; NOVA ALFIAN HARIYANTO; SUHARTINI SUWANDARI; IRMAYANTI TRI KURNIA; PREECHA PHUWAPRAISIRISAN; MUHAMMAD IQBAL HASAN; KIETTIPUM PHONTREE; JOHAN SETIAWAN; SALAMUN SALAMUN; NANANG DWI WAHONO; AGUS SUPRIYANTO; MOCH. AFFANDI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Ramadhan R, Ni’matuzahroh, Lestari DA, Hariyanto NA, Suwandari S, Kurnia IT, Phuwapraisirisan PP, Hasan MI, Phontree K, Setiawan J, Salamun, Wahono ND, Supriyanto A, Affandi M. 2024. Bioprospecting of non-timber forest products of selected flora in Baluran National Park, East Java, Indonesia for phytochemicals, anti-diabetic, anti-tyrosinase, and antioxidants. Biodiversitas 25: 3803-3815. The ecosystem within Baluran National Park comprises elements that exhibit varying degrees of sensitivity to environmental influences, encompassing both biotic and abiotic factors. It has been observed that identical plant species may display significant variations in their secondary metabolite content across different habitats. The primary objective of this investigation is to analyze the phytochemical composition, antioxidant properties, anti-tyrosinase effects, and anti-diabetic potential of specific flora species found in Baluran National Park. Furthermore, the research aims to identify novel natural resources with anti-diabetic and antioxidant properties among the selected flora from Baluran National Park, East Java, using chemotaxonomic and ethnopharmacological data. The study involved the qualitative and quantitative analysis of phytochemicals, along with assessing their in vitro anti-diabetic, anti-tyrosinase, and antioxidant activities through various assays such as ?-glucosidase inhibition, tyrosinase inhibition, and free radical scavenging tests (DPPH, ABTS, CUPRAC, and FRAP). The findings reveal that ethanol extracts of Euphorbia atoto demonstrated potent ?-glucosidase inhibitory activity with a percent inhibition (PI) value of 92.07±1.43%, surpassing the inhibitory effects of acarbose (25.92±1.61%) and quercetin (84.79±1.18%). Additionally, the antioxidant assessments indicated that the selected flora from Baluran National Park exhibited substantial antioxidant properties, as evidenced by their percent inhibition (PI) values. These results provide a scientific basis for considering the flora of Baluran National Park as a potential source of natural medicinal compounds.